Kecernaan Pakan dan Pertumbuhan Ikan Patin Pangasius hypopthalmus yang Diberi Tepung dan Ekstrak Daun Kayu Manis Cinnamomum burmannii - Mia Setiawati; Dedi Jusadi; Riska Diana (Jurnal Ilmu Pertanian Indonesia, 2016)
This research was conducted to evaluate the digestibility and growth performance of catfish Pangasius hypopthalmus fed on Cinnamomum burmannii leaf powder and extract. Ten catfish with an average body weight of 0.02 ± 11.24 g were stocked into the 40 × 50 × 35 cm aquarium. Fish were fed on the diet contained of 0.1% cinnamon extract, 1% cinnamon powder and without cinnamon leaf. Fish were fed on those diets at satiation with times a day. Fish were cultured for 60 days. The results showed the bacterial total number in the gut of fish fed diet contained 0.1% cinnamon leaf extract was 7.8 x 107 cfu/g, greater than other treatments. Protein digestibility in 0.1% cinnamon extract increase 4.12% and body protein 58.72%. The whole body of fish fed on cinnamon leaf extract contained higher protein and lower fat. There was no different result in the growth of catfish